2010
DOI: 10.1203/pdr.0b013e3181e12770
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Regulates NOS Expression in Afferent Arterioles of the Developing Porcine Kidney

Abstract: NO protection is crucial against angiotensin II (ANG II) mediated vasoconstriction in postnatal preglomerular resistance vessels. Although whole kidney NOS is developmentally regulated, NOS regulation in developing renal resistance vessels is unknown. The hypothesis was NOS expression and function in developing afferent arterioles are regulated by ANG II through AT1 and AT2 receptors. Afferent arterioles from porcine kidneys, ages newborn, 7, 21 d, and adult, were dissected using a polybead perfusion technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…The RAS influences cardiovascular function via nitric oxide (NO) regulation (6)(7)(8). AT 1 R blockade increases NO, and this increase is abolished by concomitant AT 2 R blockade, suggesting that AT 2 Rs are important in NO production (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RAS influences cardiovascular function via nitric oxide (NO) regulation (6)(7)(8). AT 1 R blockade increases NO, and this increase is abolished by concomitant AT 2 R blockade, suggesting that AT 2 Rs are important in NO production (9).…”
mentioning
confidence: 99%
“…AT 1 R blockade increases NO, and this increase is abolished by concomitant AT 2 R blockade, suggesting that AT 2 Rs are important in NO production (9). AT 2 Rs likely increase NO production via direct stimulation of NO synthase (NOS) (10) or indirectly through bradykinin-dependent mechanisms (7). Recently, the intracrine activation of AT 2 Rs has been reported to increase NO production in isolated cortical kidney nuclei (11).…”
mentioning
confidence: 99%
“…However, several characteristics of nNOS in postnatal renal maturation suggest that this isoform may participate significantly in renal hemodynamics in the neonate after birth. In previous studies by our laboratory, we observed both developmentally upregulated NOS enzymatic activity and nNOS mRNA and protein expression in the kidney during the postnatal period (19,20). In fact, NOS enzymatic activity in the preglomerular-resistance vasculature of the newborn is fourfold greater than that of the adult (19).…”
mentioning
confidence: 62%
“…NO is known to inhibit cyclic adenosine monophosphate degradation through cyclic GMP-mediated mechanisms, thereby stimulating renin secretion, whereas cellular calcium influx and protein kinase K activation inhibit renin release (36 (3,11,19). In studies by Ratliff et al, it was demonstrated that NO production in the preglomerular resistance vasculature is threefold higher in the newborn than in the adult (19,20). During the newborn's period of increased NO production, eNOS expression is minimally detectable, with protein levels sevenfold less than what is observed in the adult (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation